STRATEGY OF FINANCIAL INCLUSION DEVELOPMENT IN INDONESIA - Bedjo Santoso; Ahamed Kameel Mydin Meera (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2017)
The objective of financial inclusion (FI) to facilitate people include the poor able to access financial assistances. It is international institution conducted World Bank. Indonesia rate of FI is 32 %, this means 68% of the poor are not touched by any financial services. The average in the world FI is just 50%. FI is very important to Indonesia as the poverty Indonesia is still high (59%). FI movement in Indonesia is just started formally in 2015. Government vision, mission, and concept have been established, however, the model of FI implemented in Indonesia does not develop properly. Currently, the most literature and practices are just partial. The research on geographic and community based is being ignored. Hence, this research aims to develop a suitable model for Indonesia that is very heterogeneous in term of areas, values, traditions, customs, communities, and local wisdom. This research is a qualitative approach by conducting an interview with the stakeholders. A deductive method is used to explore and to design the proposed model. Besides that, the research employs IDC approach to design the framework. IDC includes intelligence, design, and choice. The result offered three scenarios; the appropriate model is community-based, then, a standard global model of FI, and finally, mobile payment system based on gold as a measurement of value. The using of ICT is possible, it is because ICT has been recently developed into a digital sustainable collaborative networking (DCN) platform, and it is expected to be capable of demonstrating the building of social and economic welfare, particularly in crafting innovations to facilitate marginal society. Moreover, by accommodating the community model which is implemented together with the two models will strengthen to national unity. =========================================== Inklusi keuangan adalah gerakan global dibawah program World Bank untuk membuat orang miskin mampu mengakses layanan keuangan. Tinkat pencapaian inklusi keuangan di Indonesia mencapai 32 %, ini berarti 68% orang miskin tidak terjangkau oleh layanan keuangan sedangkan rata-rata di dunia hanya 50%. Selain itu, angka kemiskinan di Indonesia adalah 59%. Oleh karena itu, Inklusi Keuangan sangat mendesak bagi Indonesia untuk mengatasi masalah ini. Sementara itu, di Indonesia, hal tersebut baru dimulai dengan mengadopsi sistem pembayaran mobile, konsep visi dan misi telah diatur oleh pemerintah. Saat ini, sebagian besar literatur dan praktek berjalan parsial. Sedangkan penelitian tentang geografis dan berdasarkan masyarakat diabaikan. Oleh karena itu, penelitian ini bertujuan untuk mengakomodasi spesialisasi Indonesia yang sangat heterogen dalam hal daerah, nilai-nilai, tradisi, adat, masyarakat, dan kearifan lokal. Penelitian ini adalah pendekatan kualitatif dengan melakukan wawancara kepada para pemangku kepentingan, metode deduktif digunakan untuk mengeksplorasi dan merancang model yang diusulkan. Hasilnya ditawarkan dalam tiga skenario; model yang sesuai berbasis masyarakat, kemudian model standar global inklusi keuangan, dan akhirnya, sistem pembayaran mobile berbasis emas sebagai pengukuran nilai. Dengan mengakomodasi model masyarakat yang diimplementasikan bersama-sama dengan dua model akan memperkuat persatuan nasional.